1998
DOI: 10.1007/s002469900335
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of Cerebral Injury from Profound Hypothermia During Cardiopulmonary Bypass

Abstract: Choreoathetosis, seizures, and impaired mental development continue to occur in children undergoing cardiopulmonary bypass (CPB) and profound hypothermia with or without circulatory arrest. Although there is some evidence that the hypothermia itself may be causing these neurologic problems, skepticism remains because of lack of evidence from experimental studies simulating the clinical setting. In this experimental study, we examined the effect of profound and moderate hypothermia on the brain while maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This may be owing to a direct effect, as deficits in perioperative cerebral perfusion predominantly exert negative influences on vulnerable brain regions such as the frontal brain lobes, hippocampus, and cerebellum. [31][32][33] Impaired neurological status and reduced endurance capacity predicted increased stress from illness as assessed by the children themselves. As in other studies, patients with cerebral palsy, ataxia, and/or global developmental delay reported particularly poor self esteem and health related quality of life, 34 35 and problems such as anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…This may be owing to a direct effect, as deficits in perioperative cerebral perfusion predominantly exert negative influences on vulnerable brain regions such as the frontal brain lobes, hippocampus, and cerebellum. [31][32][33] Impaired neurological status and reduced endurance capacity predicted increased stress from illness as assessed by the children themselves. As in other studies, patients with cerebral palsy, ataxia, and/or global developmental delay reported particularly poor self esteem and health related quality of life, 34 35 and problems such as anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the Scheidtmann, et al (2001) protocol (28) for humans by giving rats DOPA 30 minutes prior to exercise therapy in order to take advantage of the peak time of the DOPA effect. Studies of the effects of monoaminergic agents in rats following unilateral motor cortex ablation indicate that the motor recovery occurs only if physical training is performed during the peak of drug availability [30]. …”
Section: Methodsmentioning
confidence: 99%
“…10 found that PH, independent of cerebral ischemia or other factors, causes central nervous system injury in swine. Damage and loss of hippocampal neurons are prominent findings following PH with or without circulatory arrest 6,9 , similar to hippocampal damage caused by global ischemia 11 .…”
Section: Introductionmentioning
confidence: 87%
“…However, a number of laboratory studies suggest that PH/rewarming (RW) injures neurons separately from injury caused by cerebral blood flow insufficiency. For example, in dogs cooled to 12 °C during normal blood flow cardiopulmonary bypass, DeLeon et al documented extensive neurologic damage in the cerebrocortex 9 . Similarly, Watanabe et al 6 found widespread and persistent neural injury, including substantial loss of hippocampal neurons, in dogs following normal flow cardiopulmonary bypass in which the dogs were merely cooled to 20 °C and not subjected to any ischemic stress.…”
Section: Introductionmentioning
confidence: 99%